The demographic profile and referral of preschoolers with attention deficit/hyperactivity disorder (ADHD) attending a child, adolescent and family psychiatric unit - Antwi-Anyimadu, Annette (My University, 2021)
Introduction: Attention deficit/hyperactivity disorder (ADHD) is one of the most frequently investigated childhood psychiatric illnesses, but data on the condition in Africa generally lacking, particularly in the under-six age group. The aim of this study was to investigate the socio-demographic profile and referral patterns for preschool children attending a psychiatric clinic in Soweto, Johannesburg. Methods: A retrospective descriptive review was conducted to analyze data abstracted from files of under six-year old children with a diagnosis of ADHD who attended Chris Hani Baragwanath Academic Hospitals (CHBAH) Child, Adolescent and Family Unit’s (CAFU) ‘Under-six ADHD Clinic’ from 1 January 2017 to 31 December 2017. Abstracted data included information on social-demographics, referral sources and reasons for referral. Results: A total of 152 files meeting the inclusion criteria for the study we reviewed. There were significantly more males (n=117, 77%) then females. The majority (n=116, 76%) attended preschool, and more than half (n=78, 51%) hailed from dual parent homes. For most preschoolers with ADHD, household income was derived from a single source (n=65, 43%). Health professionals referred 53% (n=81) of the participants. The main reasons for referral were hyperactivity (n=65, 43%), followed by behavioral patterns (n=22, 14%), and developmental delay (n=15, 10%). Allied health professionals referred as significantly greater number of preschoolers with developmental delay (n=9), compared to health professionals who referred mainly for hyperactivity (n=44). Conclusion: Most of the findings of this study correlated with other studies conducted worldwide. Screening for ADHD at the preschool age is imperative, as nearly intervention is likely to interrupt the trajectory of the illness, which ultimately results in a high cost to the economy. Interventions such as the specific support program for Grade R teachers on ADHD recently developed in South Africa (SA) for this very indication should be further explored and expanded to different appropriate settings in creating awareness of ADHD.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Psychiatry, 2021